First-principles study of electronic and optical response properties of bimetallic-sulphide heterostructure supported dithiocarbonate complex for organic solar cells - David O. Idisi; Edson L. Meyer; Evans M. Benecha (Scientific Reports)
Abstract The use of molecular complexes in improving the transport properties of active layer materials for organic solar cells has been enormous in the recent era. The current study focuses on the transport and optical properties of dithiocarbonate-based complexes on Tin sulphide/Cobalt sulphide heterostructure. The charge transfer properties show electronegativity features for the N-butylamine complex, whereas electropositive transport features are observed for the N-dodecyl amine and mixed (N-butylamine/N-dodecylamine) complex blend. This charge transfer behaviour is consistent with typical acceptor–donor features, which are associated with metal-thiocarbamate complex transport. The optical features for dithiocarbonate-based complexes supported metal sulphide heterostructure show increased absorption and reflective plasmonic features in comparison with pristine metal sulphide heterostructure. The study proposes the incorporation of a dithiocarbonate complex as support for metal sulphide heterostructure active layer material that can be used to drive improved charge transport and localized surface plasmon resonance, which is crucial for charge transport in organic solar cell devices.